Brain and Placental Pathology in Fetal COL4A1 Related Disease. (June 2021) - Shannon, Patrick; Hum, Courtney; Parks, Tony; Schauer, GM; Chitayat, David; Chong, Karen; Shinar, Shiri; Blaser, Susan; Moore, Gaea; Van Mieghem, Tim
Introduction: Although fetal brain injury due to COL4A1 gene mutation is well documented, fetal central nervous system (CNS) and placental histopathology lack description. We report CNS and placental pathology in fetal cases with symptomatic COL4A1 mutation. Methods: We retrieved four autopsy cases of COL4A1 related disease, confirmed by genetic sequencing after fetal brain injury was detected. Results: One case was a midgestation fetus with residua of ventricular zone hemorrhage and normal placental villi. Three cases were 30-32 week gestation fetuses: two demonstrated CNS small vessel thrombosis, with CNS injury. Both demonstrated high grade placental fetal vascular malperfusion (FVM). One additionally showed villous dysmorphism, the other demonstrated mild villous immaturity. The fetus whose placenta demonstrated high grade FVM was growth restricted. A fourth fetus demonstrated schizencephaly with a CNS arteriopathy with smooth muscle cell degeneration and cerebral infarcts; the placenta demonstrated severe villous dysmorphism and low grade FVM. Discussion: These cases confirm that small vessel disease is important in producing intracranial pathology in COL4A1 mutation. We report an arteriopathy distinct from microvascular thrombosis and demonstrate that placental pathology is common in fetal COL4A1 related disease. This tentatively suggests that placental pathology may contribute to CNS abnormalities by affecting circulatory sufficiency.